Text, speech, and dialogue : 19th International Conference, TSD 2016, Brno, Czech Republic, September 12-16, 2016, Proceedings /: 19th International Conference, TSD 2016, Brno, Czech Republic, September 12-16, 2016, Proceedings. (2016) - Unknown
No abstract available